Marketing Strategy In An Effort To Increase The Number Of Members Of Savings And Loans Products In The Jasa Bintang Muda 88 Cooperative In Makale District, Tana Toraja District - Yovita Yovita; Abedneigo.C.Rambulangi (Universitas Kristen Indonesia Toraja, 2022)
The purpose of this study was to find out what marketing strategies were carried out by the Bintang Muda 88 service cooperative in increasing the number of members of the savings and loan product and to explain the explanation of the product marketing strategy savings and loans can have an impact on the development of the number of members in the young star service cooperative 88. The type of research informants 5 people. Data collection was carried out by means of observation, interviews and documentation. The research results obtained by promotion by implementing the 4P strategy (product, price, place and promotion) are proven to be able to increase the number of members in saving and loan savings at the Bintang Muda 88 service cooperative because the Bintang Muda 88 cooperative markets its products on social media such as facebook, instagram and so on and conduct outreach to various places of service. By Implementing the 4P strategy, it can have an impact on increasing the number of outstanding members by increasing the number of savings and loan members every year.